The Influence of Sharia Financial Literacy and Fintech Lending Services on the Financial Behavior of Muslim Communities - Fadillah, Aniva Nur; Suryomurti, Wiku (IJIBE (International Journal of Islamic Business Ethics), 2024)
This study was conducted to find out how financial literacy and fintech lending services affect the financial management behavior of Muslim communities. This research uses a quantitative approach and surveys 272 respondents through electronic media. This research method uses the Structural Equation Model—Partial Least Square (SEM-PLS) equation by taking a case study of Muslim communities in Indonesia. The results show that financial literacy, ease of fintech lending services, and trust in fintech lending services have a positive and significant effect on Muslim communities' financial management behavior. Meanwhile, the benefits of fintech lending services do not have a significant influence on the financial management behavior of Muslim communities. However, information is crucial in determining and making decisions. In the context of fintech lending services, speed and convenience play an essential role in shaping a person's financial behavior. Furthermore, the policy and legality of fintech lending are critical in improving public trust in the use of these services. Increased public trust in fintech lending services will have an impact on people's financial habits.